Result of cementless total hip arthroplasty in a patient with osteopoikilosis, hip dysplasia and advanced osteoarthritis: a case report - Yao-Yuan Chang; Wei-Hsin Lin (BMC Musculoskeletal Disorders, 2021)
Abstract Background Osteopoikilosis (OPK) is a rare benign sclerosing bone dysplasia and is often incidentally found on plain radiography. OPK generally does not require treatment. Nevertheless, osteonecrosis or degenerative joint disease can occur in the setting of OPK, and little is known with regard to the longevity of arthroplasty prostheses implanted into OPK-bearing bones. Case presentation A 55-year-old male presented with progressive right hip pain in 2012. He was diagnosed with coexisting osteopoikilosis and developmental dysplasia of the right hip with advanced osteoarthritis after a series of imaging studies including radiographs, magnetic resonance imaging (MRI), and bone scan. A cementless total hip arthroplasty was performed to treat his right hip pain. Radiographs at eight-year follow-up showed the prosthetic components were well-fixed. Harris hip score of the patient’s right hip was 93. The patient can walk without assistance and work as a construction worker. Conclusion Cementless arthroplasty can be considered in patients with hip arthropathies and co-existing osteopoikilosis. Continued follow-up is required to establish the long-term results.